Mammalian mitochondrial uncoupling proteins - Jezek, P; Garlid, K D (The international journal of biochemistry & cell biology, 1998)
The mammalian uncoupling protein (UCP-1) from the gene family of mitochondrial carriers is a dimer of identical 33 kDa subunits, each containing six membrane-spanning alpha-helices. Its expression, restricted to brown fat, occurs upon birth, cold acclimation and overfeeding. UCP-1 dissipates redox energy and thereby provides heat to the animal. Two additional isoforms have recently been discovered, 59% homologous UCP-2, widely expressed (heart, kidney, lung, placenta, lymphocytes, white fat); and UCP-3 (57% homologous), found in brown fat and skeletal muscle. Their physiological roles are unknown, but may include the regulation of body weight and energy balance, muscle nonshivering thermogenesis, fever, and defense against generation of reactive oxygen species. Consequently, great pharmacological potential is expected in revealing their biochemical and hormonal regulators. UCP-1 mediates a purine-nucleotide-sensitive uniport of monovalent unipolar anions, including fatty acids, that lead to fatty acid cycling and uncoupling. UCP-2 and UCP-3 are expected to share a similar mechanism.
Keywords: Molecular Sequence Data; biologický transport; membránové proteiny; Tissue Distribution; sekvence aminokyselin; Adipose Tissue, Brown; Membrane Proteins; iontové kanály; Carrier Proteins; Uncoupling Protein 1; Biological Transport; Fatty Acids; Mitochondrial Proteins; zvířata; tkáňová distribuce; Humans; Amino Acid Sequence; uncoupling protein 1; mastné kyseliny; Ion Channels; molekulární sekvence - údaje; hnědá tuková tkáň; sekvenční homologie aminokyselin; transportní proteiny; mitochondriální proteiny; lidé; Sequence Homology, Amino Acid; Animals